Crystallization-induced structure fluctuation of crystallized microdomain structure composed of strongly segregated crystalline-crystalline diblock copolymers. (12th October 2016) - Nojima, Shiki; Higaki, Yuji; Ishige, Ryohei; Kabayama, Hirofumi; Ohta, Noboru; Masunaga, Hiroyasu; Hirai, Tomoyasu; Kojio, Ken; Takahara, Atsushi
Abstract: Crystallization-induced structure fluctuations in the layer thickness direction and disordering of pre-crystallized structure in crystallized microdomain structure that consist of a strongly segregated crystalline-crystalline diblock copolymer, poly(ethylene glycol)- block -poly(perfluorooctyl ethyl acrylate) (PEG- b -PFA-C8 ), were investigated. The structure formation process during isothermal crystallization was monitored by in-situ time-resolved simultaneous SAXS/WAXD measurements and thermal analysis. At early stage of isothermal crystallization, three dimensional growth of the PEG lamellar crystals within lamellar microphase-separated morphology induced the volume shrinkage of PEG phase, resulting in the reduction of PEG layer thickness, increase of PFA-C8 layer thickness and disordering of pre-crystallized PFA-C8 crystals. At late stage of isothermal crystallization, one dimensional growth, thickening of PEG lamellar crystals induced the increase of PEG layer thickness and reduction of PFA-C8 layer thickness. The structure fluctuation in the crystallized microdomain structure depends on the crystal growth dimension. Graphical abstract: Highlights: Structure building process in a double crystalline block copolymer was clarified. Crystallization-induced structure fluctuation was studied by SAXS/WAXD. Crystal growth dimension dominates the structure fluctuation.